2022
DOI: 10.3390/ijms23147821
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Diffuse Gastric Cancer: Molecular Genetics, Biological Mechanisms and Current Therapeutic Approaches

Abstract: Hereditary diffuse gastric cancer is an autosomal dominant syndrome characterized by a high prevalence of diffuse gastric cancer and lobular breast cancer. It is caused by inactivating mutations in the tumor suppressor gene CDH1. Genetic testing technologies have become more efficient over the years, also enabling the discovery of other susceptibility genes for gastric cancer, such as CTNNA1 among the most important genes. The diagnosis of pathogenic variant carriers with an increased risk of developing gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…As such, the surgical removal of all gastric mucosa can be challenging. There were two studies that reported a need for reintervention due to incomplete removal of the gastric mucosa at the proximal resection margin [25,38]. In line with these findings, intraoperative confirmation of the squamous mucosa in the proximal oesophageal and duodenal mucosa in the distal margins is recommended in the international guidelines to ensure complete removal of the gastric mucosa [6].…”
Section: Discussionmentioning
confidence: 89%
“…As such, the surgical removal of all gastric mucosa can be challenging. There were two studies that reported a need for reintervention due to incomplete removal of the gastric mucosa at the proximal resection margin [25,38]. In line with these findings, intraoperative confirmation of the squamous mucosa in the proximal oesophageal and duodenal mucosa in the distal margins is recommended in the international guidelines to ensure complete removal of the gastric mucosa [6].…”
Section: Discussionmentioning
confidence: 89%
“…A few molecular germline mutations are currently recognized as causal events related to these cases [ 29 ]. There are formal recommendations for carriers and their relatives in these situations [ 30 , 31 ]. Nonetheless, many young GC patients do not have such mutations, as is the case in the 95 GC patients under 50 years old discussed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increased risk of gastric cancer associated with CDH1 mutation, ranging up to 70% in men and 56% in women, appropriate screening measures should be taken into consideration in a timely manner [17].…”
Section: Tubularmentioning
confidence: 99%